High-pressure processing treatment of beef burgers: Effect on Escherichia coli O157 inactivation evaluated by plate count and PMA-qPCR - Rey, Maria De Los Angeles; Rodriguez, Anabel; Rossi Ribeiro, Luma; Dos Santos Cruz, Fabiano; Cap, Mariana; Mozgovoj, Marina Valeria; Cristianini, Marcelo; Vaudagna, Sergio Ramon (Wiley, 2022)
Este trabajo fue apoyado por el Ministerio de Ciencia y Tecnología, Agencia Nacional de Promoción de la Investigación, desarrollo tecnológico y la innovación (MINCYT PICT-2015-0291).